Pengelolaan Tanah dan Air Berbasis Kearifan Lokal Untuk Mencegah Bencana Alam Longsor - Andani Putri; Febriyana Putri; Erni Suprihani (UM Purwokerto Press, 2021)
Village governments are required to be able to respond to public needs, one of which is disaster. It needs a quick response attitude from stakeholders as an effort of mutual obligation, one of which is the important role of the village government. Local wisdom is formed as a cultural superiority of the local community and a characteristic of cultural values in local communities that is passed down from generation to generation. This study aims to determine the role of the village government and local wisdom of the community in mitigating landslides in Gununglurah Village, Cilongok District, Banyumas Regency. The method used in this research is survey. Types of data include primary data and secondary data. Data collection through in-depth interviews. Data analysis using descriptive qualitative method. The results showed that the community had to carry out good land and water management based on local wisdom, including mountain hives, agro-ecosystem approaches, forbidden forest preservation, application of intercropping agricultural patterns, and the presence of the Watu Langgar Kali Mengaji site. The community must maintain the values of local wisdom in mitigating landslide disasters, such as the knowledge that comes from “ilmu niteni”.